English for general purposes (EGP) as a means to improve undergraduate freshmen’s language proficiency in Taiwan - Huang, Shu-Hsiu; Tsai, Kuei-Ju (International journal of educational development, 2024)
In Taiwan, English is termed English for General Purposes (EGP) and is a mandatory subject for university students as part of their general education curriculum. Despite previous discussions on various issues related to EGP, there is limited research on students' overall learning effectiveness of EGP and the influence of language proficiency and gender on EGP learners' learning outcomes. This study collected and analyzed the English test scores of over 2000 undergraduate first-year students from three consecutive academic years. The results indicate that many students showed noticeable progress after receiving EGP instruction. The improvement was more significant for female students than male students, with female students at elementary and intermediate levels most benefiting from the EGP learning experience. •Students made considerable progress after receiving a year of English for general purposes instruction.•Female students improved more than males.•Females at elementary and intermediate levels benefited the most from the EGP learning experience.•Grouping EGP instruction had a positive impact on the mastery of English for the students.